Pemberdayaan Masyarakat Berbasis Modal Sosial Dalam Rangka Pelestarian Hutan Mangrove - Arif Ferdian; Syamjaya SM; Darmawati Darmawati (SOCIETAS, 2021)
The area of the North Luwu mangrove forest is 16,000 hectares. With a coastline length of 53 Km.However, 24% of the mangrove ecosystem is in a damaged condition. The damage was spread overseveral points. One of the points of concern is the coastline area of Pao Village and Pengkajoan Village.The damage was caused by the conversion of mangrove forest land for milkfish and shrimp ponds,changing the function to agricultural land, especially citrus farming, residential areas, and plantationland. This study aims to analyze community empowerment through the concept of social capital toconserve mangrove forests. This type of research is a descriptive type of research with a qualitativeapproach. Data collection was carried out through interviews, observation, and documentation.Activities in the analysis consist of data condensation, data display, and conclusion drawing/verification.The results showed that social capital-based community empowerment in mangrove conservation hasbeen running, this is because the group can move its members in preserving mangrove forests by onlycapitalizing on mutual trust by prioritizing group goals. Besides that, what makes the group empoweredis the collaboration with the local government and universities in Luwu Raya. The increase in groupcapacity is also due to training and mentoring from universities, especially regarding the impact ofchanging mangrove forest lands.